Pengaruh Pembelajaran Daring, Lingkungan Keluarga dan Pendidikan Orang Tua Terhadap Hasil Belajar Siswa Kelas XI Ekonomi SMA Negeri 1 Bonjol - Putri Putri; Syamwil Syamwil (Jurnal Salingka Nagari, 2023)
The purpose of this research is to investigates the effect of online learning, family environment and parental education on student learning outcomes in class XI Economics at SMA N 1 Bonjol. The type of research is associative. The population in this study were 132 respondents and the number of samples using the Slovin formula was 100 samples. Data was collected by distributing questionnaires to class XI students with predetermined criteria. The data was be analysed with multiple regression analysis. The results is (1) online learning, family environment and parental education have significant effect on economic learning outcomes for class XI student of SMA N 1 Bonjol, and parents families has no significant effect on learning outcomes (2) online learning have significant effect on result (3) family environment have significant effect on learning outcomes (4) parental education don’t have significant effect on student learning outcomes for class XI Economics at SMA N 1 Bonjol.